Customer satisfaction in Malaysian Takaful Industry / Nurul Liyana Mohd Razali. - Mohd Razali, Nurul Liyana (2020)
Customer pride is essential as studies exhibit that a comfortable client will share their ride with other people, they unfold a good ‘word-of-mouth’ and this mind-set addition-ally will assist to lower the value of attracting a new clients and for the upset customer, they will act the other way and has the contrary effect. The goal of this paper is to examine a range of determinants of client satisfaction based on current literature. At the equal time, the history of the development of the Takaful Insurance Industry has been revealed in the context of Malaysia because the study of purchaser satisfaction, in par-ticular in the Takaful Industry in Malaysia, is nonetheless limited; therefore, the re-searcher tries to convey the total definition of client satisfaction based totally on the findings of the preceding lookup.